Les altérations des vins par les bacteries acétiques et les bactéries lactiques - Suzanne Lafon-Lafourcade; Pascal Ribéreau-Gayon (OENO One, 1984)
Acetic acid and lactic acid bacteria were present at all stages of wine making. A lower pH and a highter ethanol concentration limit the risks of alteration. During the conservation, a low temperature, good use of S02 and frequent checkings ensure control of bacterial growth and metabolism.